Rejuvenating Islamic thought - Abd. Rahman, Akmal Khuzairy (IIUM Press, International Islamic University Malaysia, 2018)
This book content selected research papers which were submitted to the 3rd International Social Science Conference - Islamic Thought and Understanding (ISSCITU 2018), organized by Universiti Teknologi Mara Perlis (UiTM) and the Office of Sultan Haji Ahmad Shah Mosque, International Islamic University Malaysia. It addresses the ideas of promoting peaceful Islam and strengthening the spiritual dimensions of faith and practice. Hence the book focuses on the role of Islamic institutions in rejuvenating Islamic thought and understanding. It is hope to be a platform for Muslims discussions on contemporary issues, challenges and solutions.